Improving binary classifiers on imbalanced data using large language models - BARBOSA, José Matheus Lacerda (2023)
In the realm of real-world classification tasks, the challenge of imbalanced data fre- quently hinders the efficacy of machine learning models in performing accurate binary classifications. To address this issue directly, this study introduces "BALANCE," a novel framework designed to rectify data imbalance in text datasets for binary classification. BALANCE leverages prompt-based learning to efficiently generate synthetic data that mimics the characteristics of the minority class. This is achieved by optimizing the de- coding parameters of a specific natural language generation model and tailoring text gen- eration to the minority class. A customized prompt is subsequently employed to generate instances using the fine-tuned language model. We conducted a comprehensive experimen- tal evaluation using three imbalanced real-world text classification datasets. The findings of our study reveal that BALANCE consistently outperforms existing methods for data creation and imbalance correction in the majority of scenarios. These results underscore the high quality of the generated instances and the potential of BALANCE to significantly enhance the performance of text classification models when dealing with imbalanced data.